The Role of Language Severity and Education in Explaining Performance on Object and Action Naming in Primary Progressive Aphasia - Riello, Marianna; Faria, Andreia V.; Ficek, Bronte; Webster, Kimberly; Onyike, Chiadi U.; Desmond, John; Frangakis, Constantine; Tsapkini, Kyrana (Frontiers in Aging Neuroscience, 2018)
Despite the common assumption that atrophy in a certain brain area would compromise the function that it subserves, this is not always the case, especially in complex clinical syndromes such as primary progressive aphasia (PPA). Clinical and demographic information may contribute to PPA phenotypes and explain the manifested impairments better than atrophy. In the present study, we asked how much variance of the object and action naming impairments observed in PPA may be attributed to atrophy in the language network alone vs. additional clinical and demographic factors including language severity and education. Thirty-nine participants with PPA underwent magnetic resonance imaging (MRI) for volumetric analysis and a complete neuropsychological examination, including standardized tests of object and action naming. We used stepwise regression models to compare atrophy (volumetric model) to clinical/demographic variables (clinical-demographic model) for naming objects and actions. The clinical-demographic model was the best-fit model that explained the largest amount of variance in both object and action naming. Brain volume measurements alone explained little variance in both object and action naming. Clinical factors, particularly language severity, and demographic factors, particularly education, need to be considered in conjunction with brain volumes in PPA. The present study emphasizes the complexity of PPA as a syndrome and provides an example of how volumetric, clinical and demographic factors may interact in determining naming performance/deterioration.